Neutrophil functions in morbidly obese subjects - Brotfain, E.; Hadad, N.; Shapira, Y.; Avinoah, E.; Zlotnik, A.; Raichel, L.; Levy, R. (Clinical and experimental immunology, 2015)
Summary The present study aimed to determine different peripheral blood neutrophil functions in 18 morbidly obese subjects with body mass index (BMI) ranging between 35 and 69 kg/m2 in parallel with age‐ and gender‐matched lean controls. Peripheral blood neutrophil functions of obese subjects and matched lean controls were determined. Neutrophils of obese subjects showed significant elevation of the release of basal superoxides (P < 0·0001), formyl‐methionyl‐leucyl‐phenylalanine (fMLP)‐stimulated superoxides (P < 0·0001) and opsonized zymosan (OZ)‐stimulated superoxides (P < 0·045) compared with lean controls. Interestingly, there were no differences in phorbol myristate acetate (PMA)‐stimulated superoxide production by neutrophils of the obese subjects and controls. There was also a significant elevation of chemotactic (P < 0·0003) and random (P < 0·0001) migration of neutrophils from obese subjects compared with lean controls. Phagocytosis, CD11b surface expression and adherence of neutrophils from obese subjects were not significantly different from those of the lean controls. The elevated superoxide production and chemotactic activity, together with the normal phagocytosis and adherence, suggest that neutrophils from obese subjects are primed and have the capability to combat infections. However, neutrophils in the priming state may participate in the pathogenesis of obesity‐related diseases.